Is there an alternative to voluntary export restraint arrangements? - Wilfried Gatzke (Intereconomics, 1989)
Against the background of the increasing proliferation of voluntary export restraint arrangements, a proposal put forward by the American economist C. F. Bergsten recommending an alternative system of auction quotas is currently the subject of international discussion. Our article gives a critical examination of this potential new instrument of international trade policy.
Keywords: 330; Auction Quotas